Production of Bio-Ethanol from the Organic Fraction of Municipal Solid Waste and Refuse-Derived Fuel - Roland Verhe; Saju Varghese; Johan M. Thevelein; Jasmijn Hazegh Nikroo; Margaux Lambrecht; Emile Redant; Gilles De Clercq (Biomass, 2022)
The organic fraction of municipal solid waste (OFMSW) and refuse-derived fuel (RDF) mainly consisting of paper/cardboard can be used as feedstock for the production of cellulosic ethanol. In this paper, an efficient technology is described to convert waste paper/cardboard into cellulosic ethanol. The process involves separation of the OF from the other components in the waste stream. An acid pretreatment is used to liberate the cellulosic fibers and the accessibility of the enzyme Cellic CTEC3 loading 3.75–11.25 FPU/g paper in a fed-batch addition up to 22.5% solid yield, 15 g sugars/l with a saccharification yield up to 90%. A semi-simultaneous fermentation process (SSFP) with a saccharomyces cerevisae strain MDS130 capable of fermenting both pentoses and hexoses are growing an ethanol titer (%v/v) of 8.4% on pilon-plant scale.